Penerapan Algoritma Genetika untuk Memprediksi Penjadwalan Jasa Pasang Pada PT. Reka Graha Semesta - Aida Septiani Aida; Nilma; Siti Julaeha (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The installation service scheduling stage is the most important stage in ensuring the company's operational efficiency, especially in the service industry which involves the repair or installation of various products or services. In addition, scheduling installation services is a complex challenge, this is because it involves the allocation of resources, time and priorities to complete various installations and avoid conflicts. To overcome the complexity of scheduling problems, genetic algorithms have become an attractive and effective approach, because they can solve multi-criteria and multi-objective problems to solve problems that are modeled by biological and evolutionary processes. The genetic algorithm represents the candidate scheduling solution into a chromosome at random and will be evaluated using the fitness function, after which selection is carried out, then crossing over or mutation is carried out. Then in each generation the chromosomes are evaluated based on the value of the fitness function, so the genetic algorithm will produce the best chromosome or is an optimal solution approach. System implementation in this study uses web-based applications to make it easier to use because there is no installation process from the user's side, and the programming language used is Hypertext Preprocessing (PHP), and MySQL as a database that makes it easier to store data that is safe and easy to access.